Validity of expired gas dynamics model during intermittent load exercise - Takahashi, S.; Chiba, T.; Ishii, H.; Nishijima, T. (International Journal of Sport & Health Science, 2005)
The purpose of this study was to determine a predictive validity of an expired gas dynamics (EGD) model during intermittent exercise using by system dynamics, individually. Five healthy males performed an incremental exercise test to determine maximal oxygen uptake (VO2max) and anaerobic threshold (AT). Subjects then undertook intermittent load tests with three degrees of intensity (60 %VO2max, 80 %VO2max and 100 %VO2max) using cycle ergometer. The EGD model was constructed using the incremental load test data. Data obtained from intermittent load tests were used as validity criterion of simulation. In simulation of the EGD model, oxygen uptake (VO2), carbon dioxide output (VCO2) and lactate (La) showed significantly high determination coefficient to validity criterion (R2 > 0.84, P < .05). In the comparison of simulation errors, there were no significant differences in VO2, VCO2 and La during 60 %VO2max intensity exercise. At recovery period of 80 %VO2max and 100 %VO2max intensities simulation errors of VO2 and VCO2 were significant. It was inferred that time constant of VO2 kinetics was slowed down by effect of excess post-exercise oxygen consumption (EPOC). Conclusively, the EGD model for individual was valid and accurate predictor of VO2, VCO2 and La during moderate intermittent load exercise.